The Correlation of Anthocyanin Levels, Vitamin C Levels, and Antioxidant Activity of Purple Cabbage (Brassica Oleracea L.) Juice at Different Temperatures and Storage Periods - Crescentiana Emy Dhurhania; Diah Pratimasari; Maliny Kurnia Salwa; Shinta Pasmawati; Muhammad Yusril Ihza Ramadhan (Indonesian Journal of Global Health Research, 2022)
Purple cabbage (Brassica oleracea L. var. capitata f. rubra) is a plant from the Brassicaceae or Cruciferae family that can be grown in both highlands and lowlands. The amount of purple cabbage production is relatively high, but utilization by consumers is still low. The choice of how to use purple cabbage is to make juice, because it is easy to make and only takes a short time, and the freshness can still be enjoyed. The way of consuming juice is seen as more relevant and enjoyable for the general public than having to eat large amounts of purple cabbage. Anthocyanins and vitamin C are water-soluble compounds that have a major role in providing antioxidant activity of purple cabbage juice. Both anthocyanins and vitamin C are compounds that are easily oxidized by O2 in the air so that the length of contact with air during storage will affect their stability. Likewise, storage temperature is a factor that affects the stability of anthocyanins and vitamin C which will have an impact on their antioxidant activity. Therefore, this study was conducted to determine the correlation of anthocyanin levels, vitamin C levels, and antioxidant activity of purple cabbage juice at different temperatures and storage periods. Determination of anthocyanin levels, vitamin C levels, and antioxidant activity was carried out by UV-Vis spectrophotometry. On the 7th day of storage, the anthocyanin content decreased by 3.7% at cold temperature and 22.5% at room temperature; vitamin C content decreased by 59.1% at cold temperature and 75.7 at room temperature; antioxidant activity decreased with an increase of 9.8% IC50 at cold temperature and 24.9% at room temperature. Purple cabbage juice decreased its antioxidant activity after the crop was stored for 4 days and 7 days, both stored at cold and room temperature. This was caused by a decrease in the content of the main antioxidant compounds in purple cabbage, namely anthocyanins and vitamin C, during the storage process.